Design considerations for a pulse line ion accelerator (PLIA)‐based PET isotope generator. Issue 8 (6th July 2018) - Westerly, David C.; Behbahani, Reza A.; Kavanagh, Brian; Liu, Arthur; Miften, Moyed; Serkova, Natalie J.; Diot, Quentin
Abstract : Purpose: Positron emission tomography (PET) imaging remains limited due to the cost associated with on‐site production of short half‐life, positron‐emitting isotopes. In this work, we examine the use of a pulse line ion accelerator (PLIA) to accelerate protons for single‐dose PET isotope production. Methods: Time‐domain electromagnetic field and particle‐in‐cell (PIC) simulations were performed for a 1.5‐m PLIA structure modeled in CST Microwave Studio and Particle Studio software. Scaled measurements from a kV ramp‐pulse generator were incorporated into the simulations to accelerate a 1 A, 50 ns proton beam injected with initial kinetic energy of 100 keV. A uniform, 3 T, solenoidal magnetic field was used to provide external beam focusing. Electromagnetic fields and particle phase space were recorded with ns resolution for subsequent analysis. Results: Applying a scaled 100 kV, 20 ns ramped voltage pulse to the PLIA input resulted in a travelling electric field wave inside the structure with accelerating gradient of 2.4 MV/m. The observed wave speed was 1.2 × 10 7 m/s and is in good agreement with theoretical predictions. Phase space monitors showed both acceleration and bunching of the proton beam, with a maximum kinetic energy of 2.5 MeV, observed at the exit of the single PLIA stage. Evaluation of beam position monitors at different locations in the accelerator showed bunch compression and minimal beam divergence, illustrating that the 3 T field is adequate to contain the beam over the length of the PLIA structure. Conclusion: Simulations performed in this work demonstrate the feasibility of using a PLIA structure to accelerate protons with MV/m level gradients. Combining several PLIA stages in series could allow for a low‐cost accelerator suitable for dose‐on‐demand PET isotope production.